1989
DOI: 10.1149/1.2096439
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Deposition onto a Gold Substrate

Abstract: Arsenic deposition onto a gold substrate was studied as a function of pH, deposition potential, and time. Deposition of less than three monolayers was observed. The rate of deposition decreased as the thickness of the deposit increased. A set of partial reactions leading to arsenic deposition was proposed. The kinetics of deposition at the most cathodic potentials corresponds to a high-field deposition mechanism.Arsenic is a semimetal which has the ability to reduce the grain size in gold electrodeposits (1-3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 9 publications
3
21
0
Order By: Relevance
“…Therefore, additional Au deposition can only occur at new sites on the surface. 64 Effect of Au Coverage on the As Stripping Peak Current. The effect of the Au coverage on the As stripping peak current was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, additional Au deposition can only occur at new sites on the surface. 64 Effect of Au Coverage on the As Stripping Peak Current. The effect of the Au coverage on the As stripping peak current was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical deposition should be a promising and convenient method to remove the arsenic from aqueous solution and realize the recycling usage of leaching solution. A lot of efforts [2][3][4][5][6][7][8] have been done to investigate the electrochemical behavior of arsenic in aqueous solution, as well as the deposition rate and current efficiency of elementary As. It has been found that toxic gas arsine will be produced as by-product during the electrodeposition of elementary arsenic [9,10], which has become a very important issue for the study of arsenic deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively good detection capabilities were achieved in the above ASV methods at gold electrodes. However, the mechanism of the electrochemical reaction occurring during the deposition and stripping of arsenic deposited on gold electrodes was seldom studied [39]. Therefore, the study of electrochemical reduction mechanism of arsenic species is of both theoretical and practical significance.…”
Section: Introductionmentioning
confidence: 99%